If an ontologist could speak we couldn't understand him. Issue 4 (19th May 2018) - Hewitt, Simon
Abstract: It is common for contemporary ontologists to claim that they are not concerned with what exists simpliciter, but rather with what exists 'fundamentally', or what 'really' exists. I argue that positions of this sort cannot satisfy reasonable constraints concerning the acquisition of language. I assess and dismiss possible responses to this complaint before commenting on the prospects for a metaphysics without bespoke existence claims.